Hot electron-driven chemical reactions: A review - Si Woo Lee (Applied Surface Science Advances, 2023)
Fundamental understanding of energy dissipation on surfaces has been important issues for studying renewable energy conversion. An energetic electron with high kinetic energy can be produced by a non-adiabatic dissipation process when the surface is exposed to external energy, such as exothermic reaction, mechanical interaction, or photon absorption. Excited electrons with an energy of 1–3 eV that are not in thermal equilibrium in metal surfaces are called ''hot electrons''. Significantly, it has been reported that several surface reactions such as dissociation, selective oxidation, and desorption can be driven and enhanced by the transfer of hot electrons to the catalyst surface (''hot electron-driven chemical reaction''). In this review, electronic control of chemical reactions via hot electron transfer on metal-semiconductor hybrid nanocatalysts is discussed. We show recent studies of enhancement of catalytic performance on nanostructures coupled with surface plasmon resonance, in which the transfer of hot electron is the critical pathway. The strong correlation between hot electron transfer and turnover rates proposed that excited electrons can be utilized for controlling catalytic performance. Therefore, the dissipation from photon to electrical energy, photon-driven hot electron excitation, enables to give further insight into energy conversion, considering hot electrons as a major candidate.